Effect of drying conditions on the structure of three-dimensional N-doped graphene and its electrochemical performance. Issue 26 (22nd March 2015) - Wang, Zhao; Tang, Zhihong; Han, Zhuo; Shen, Shuling; Zhao, Bin; Yang, Junhe
<x xml:space="preserve">Abstract</x> The effect of drying conditions on the structure of graphene based 3D materials is discussed in the manuscript.